Nationalization of Education in Pakistan: Z. A. Bhutto’s Policy and Implementation - Mahboob Hussain and Yawar Haroon (Journal of Political Studies, 2014)
The history of education in Pakistan is the most significant topic which needs to be highlighted and examined. This paper thoroughly describes and explains various vistas of the policy of Nationalization of education that was adopted by Prime Minister Zulfikar Ali Bhutto in 1972. The policy of Nationalization of education left long lasting impact on Pakistan’s society and culture. The paper also covers the effect of the policy on teachers and students and their reaction to the policy has been recorded historically. While there were some merits of the policy it also created difficulties for the educational institutions. These merits and demerits of the policy have also been studied in the course of discussion.